Analysis of Teachers' Difficulties in Developing Teaching Modules for the Merdeka Curriculum in Grade V Civics Subjects at Al-Islam 2 Jamsaren Elementary School, Surakarta - Alethea Otsu Khoirunisa; Annisa Diah Ramadhani; Annisa Nurul Hidayah; Rawanoko, Endrise Septina (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
The merdeka curriculum is designed to provide teachers with flexibility in organizing and performing learning that is more relevant to the needs of the students. However, the implementation of the curriculum presents various challenges, especially in the drafting of the teach module. The study was conducted to analyze the difficulties encountered by the teacher in setting up the free curriculum teach module on pancasila and cidal (ppeng) at al-islam elementary, surakarta. The research methods used are qualitative in collecting data through observation and interviews for a ppnonal subject. Research results suggest that the main challenge lies in understanding the curriculum, learning paradigm change, technological mastery, and the limitation of learning and time resources. These difficulties hinder the teacher from organizing effective teaching modules and in accordance with the principles of the free curriculum. This study suggests that training and intensive counseling can be used to help teachers overcome those obstacles.